Peran Sultan Osman Al Sani Perkasa Alam dalam Transisi Politik Kesultanan Deli Pasca Kemerdekaan Indonesia 1945–1967 - Pratama, Risky; A, Achiriah; Nasution, Katsron (Madani: Jurnal Ilmiah Multidisiplin, 2025)
During the reign of Sultan Osman Al Sani Perkasa Alam in the post-independence political transition of the Deli Sultanate (1945–1967), a radical shift occurred from a monarchical system to a republican system that rejected feudalism. The Deli Sultanate, as a traditional institution, experienced significant social and political pressure, particularly during the 1946 Social Revolution, which led to the collapse of many sultanates in East Sumatra. However, Sultan Osman was able to maintain the existence of the Sultanate through non-confrontational strategies and a cultural approach. This study aims to examine how Sultan Osman adapted to national political dynamics and how he preserved Malay cultural identity amid crisis. The research employs a qualitative method with a historical approach, collecting data through documentation, field observations, and interviews. The analysis uses theories of political transition and power legitimacy. The findings indicate that despite losing formal political power, Sultan Osman continued to play an important role as a cultural symbol, social unifier, and guardian of Malay traditional values. He represents a successful example of the transformation of traditional elites in facing changing times in a peaceful and dignified manner.